Bisphosphonate Treatment Ameliorates Chemotherapy-Induced Bone and Muscle Abnormalities in Young Mice - Essex, Alyson L.; Pin, Fabrizio; Huot, Joshua R.; Bonewald, Lynda F.; Plotkin, Lilian I.; Bonetto, Andrea (Frontiers in Endocrinology, 2019)
Chemotherapy is frequently accompanied by several side effects, including nausea, diarrhea, anorexia and fatigue. Evidence from ours and other groups suggests that chemotherapy can also play a major role in causing not only cachexia, but also bone loss. This complicates prognosis and survival among cancer patients, affects quality of life, and can increase morbidity and mortality rates. Recent findings suggest that soluble factors released from resorbing bone directly contribute to loss of muscle mass and function secondary to metastatic cancer. However, it remains unknown whether similar mechanisms also take place following treatments with anticancer drugs. In this study, we found that young male CD2F1 mice (8-week old) treated with the chemotherapeutic agent cisplatin (2.5 mg/kg) presented marked loss of muscle and bone mass. Myotubes exposed to bone conditioned medium from cisplatin-treated mice showed severe atrophy (-33%) suggesting a bone to muscle crosstalk. To test this hypothesis, mice were administered cisplatin in combination with an antiresorptive drug to determine if preservation of bone mass has an effect on muscle mass and strength following chemotherapy treatment. Mice received cisplatin alone or combined with zoledronic acid (ZA; 5 g/kg), a bisphosphonate routinely used for the treatment of osteoporosis. We found that cisplatin resulted in progressive loss of body weight (-25%), in line with reduced fat (-58%) and lean (-17%) mass. As expected, microCT bone histomorphometry analysis revealed significant reduction in bone mass following administration of chemotherapy, in line with reduced trabecular bone volume (BV/TV) and number (Tb.N), as well as increased trabecular separation (Tb.Sp) in the distal femur. Conversely, trabecular bone was protected when cisplatin was administered in combination with ZA. Interestingly, while the animals exposed to chemotherapy presented significant muscle wasting (-20% vs. vehicle-treated mice), the administration of ZA in combination with cisplatin resulted in preservation of muscle mass (+12%) and strength (+42%). Altogether, these observations support our hypothesis of bone factors targeting muscle and suggest that pharmacological preservation of bone mass can benefit muscle mass and function following chemotherapy.